PENGARUH KINERJA KARYAWAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN PT KIW BATAM - Imelda Tamba; Dini; Josepin Harianja (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
This researches has been done to analyzed whether is a positive effect and significant employee performance and product quality to the consumers’s satisfaction of PT KIW. Data  was taken from the consumers of PT KIW. Who are using KIW trade mark painting in number 50 responden with criterian as a painting the data was processed by T test and F test. The result of the research shows that the employees work has a positive and significant effect the consumers’s satisfaction as 5,886 or 588,6% and the product quality positive has been effect to consumers’s satisfaction as 2,985 or 298,5%. So, the employees work and product quality simultaneously have a positive significant effect to the consumer’s satisfaction as 96,4%.